Impact of Different IPM Modules on Natural Enemies of Helicoverpa armigera (Hubner) in Pigeonpea Ecosystem in Andhra Pradesh, India - Kavitha, K.; Reddy, D. J.; Rahman, S. J. (International Journal of Bio-resource and Stress Management, 2023)
Some IPM modules were field evaluated against Helicoverpa armigera and impact of these modules were worked out on its natural enemies in pigeon pea at ARS, Tandur during kharif 2007-08, extent of damage caused by H.armigera and yield attributes were also worked out. The results revealed that Bio Intensive Pest Management (BIPM) module was ultimately the promising one with better net returns (Cost:Benefit ratio 1:1.20) and effective conservation of natural enemies even though, Farmers Practice (FP) and Integrated Pest Management (IPM) modules initially hosted less larval populations and minimum extent of damage indicating the suitability and feasibility of BIPM for pigeon pea ecosystems by augmenting natural enemies.